Opportunistic Screening for Exposure to Bullying in the Pediatric Emergency Department - Marlene Seltzer MD; Margaret Menoch MD; Charity Chen MS (SAGE Publishing, 2017)
To assess opportunistic screening for exposure to bullying in the pediatric emergency department (ED), an anonymous survey inquiring about exposure to physical, verbal, social, and cyber bullying behaviors was given to ED patients 5 to 18 years old. The survey asked about being the recipient, perpetrator, and/or witness of bullying; the frequency of exposure; liking school; missing school; and presenting complaint. Either the child or parent could complete the survey. A total of 909 surveys were analyzed. Exposure was 78.7%. A greater proportion of females reported being victims and witnesses. Youth who reported being both victims and witnesses represented the largest group, with witness-only the second largest. Parents reported less cyber-bullying and witness status to all types of bullying. For children who did not like school, there was a significant difference in exposure versus nonexposure. There was no association with presenting complaint. Opportunistic screening for bullying exposure in pediatric ED patients warrants consideration as it may increase detection of preclinical status and clinical sequelae.